An ARDL Bounds Testing Approach to the Relationship between Financial Development and Output Growth in Nepal (PYC Nepal Journal of Management, 2018)
This paper examines the relationship between financial development and output growth in Nepal over 42 years of period from mid- July 1975 to 2017 using ARDL bounds testing approach to co-integration. The study uses natural logarithm of per capita real GDP as a proxy of output growth and means removal average of broad money (M2) to GDP ratio and domestic private credit to GDP ratio as a proxy of financial development indicator. The results of ARDL bounds test show that financial development and output growth in Nepal is co-integrated over the study period. The study results demonstrate that financial development in Nepal leads to output growth in the long-run. However, the study fails to detect any impact of financial development on output growth in Nepal over the short-run. Based on long run results of this study, it can be concluded that development of financial sector in Nepal can stimulate long-run output growth. Thus, considerable efforts should be paid on promoting the development of the financial sector that contributes significantly to achieve long-run output growth.